Note on the distribution of some lichenized and lichenicolous fungi of the Tatra National Park - Adam Flakus (Acta Mycologica, 2013)
New data about the occurrence of 25 species of rare lichens and 3 lichenicolous fungi in the Tatra National Park (Western Carpathians) are provided. Of these species, Fellhaneropsis vezdae is recorded for the first time from the whole Tatra Mts. and Vezdaea stipitata is new to the Polish Tatra Mts. The distribution of the species in the Tatra National Park is indicated.